Credit Unions as Channels of Micro-Credit Lines: The Philippine Case - Mario B. Lamberte (Philippine Institute for Development Studies (PIDS), 1995)
One of the important weapons the government has used to alleviate poverty is its credit policy aimed to mitigate destitution among small farm households. However, its intended recipients have not properly received the effort. Convinced that credit availability can be sustained to achieve poverty alleviation, the government has started to utilize informal financial institutions as credit conduits. This paper provides empirical support whether or not this strategy has been effective. In particular, it analyzes the performance of credit unions in terms of savings mobilization, credit allocation and profitability.
Keywords: 330; savings mobilization; credit unions; financial system; interest rate; credit policy; credit channel/conduit; self-employment; savings deposit; profitability and feasibility